2012
DOI: 10.1007/s10803-012-1734-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Participation in Employment for High School Leavers with Autism

Abstract: This study aimed to identify the factors associated with participation in employment for high school leavers with autism. A secondary data analysis of the National Longitudinal Transition Study 2 (NLTS2) data was performed. Potential factors were assessed using a weighted multivariate logistic regression. This study found that annual household income, parental education, gender, social skills, whether the child had intellectual disability, whether the child graduated from high school, whether the child receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(117 citation statements)
references
References 17 publications
7
103
2
5
Order By: Relevance
“…Similar to the results of Chiang et al (2012) and Chiang et al (2013), and Knott and Taylor (2014), personal expectations of academic achievement as well as social participation is equally as important to students with AS as it is for NT students. In Knott and Taylor's study, (ibid, 416) both staff and students reported a need for 'support for academic development'.…”
Section: Formal Supportsupporting
confidence: 73%
“…Similar to the results of Chiang et al (2012) and Chiang et al (2013), and Knott and Taylor (2014), personal expectations of academic achievement as well as social participation is equally as important to students with AS as it is for NT students. In Knott and Taylor's study, (ibid, 416) both staff and students reported a need for 'support for academic development'.…”
Section: Formal Supportsupporting
confidence: 73%
“…Most recently, research by Chiang et al (2013) investigated predictive factors for participation in employment for high school leavers with autism (N=830) aged between 13 and 16 years old. The predictors of employment identified were annual household income, parental education, gender (females were more likely to participate in employment), social competence, presence of a comorbid intellectual disability (ID), graduation from high school, and whether the participant's school liaised with postsecondary vocational training programs or potential employers.…”
Section: Resultsmentioning
confidence: 99%
“…Individual characteristics and employment service characteristics were found to predict employment in the studies reviewed. Two studies reported that being male was a predictor factor for employment (Lawer et al 2009;Migliore et al 2012) while Chiang et al (2013) found that females were more likely to find employment. Increased age in adulthood was also found to be a predictor of employment (Lawer et al 2009;Schaller and Yang 2005) as well as the absence of any comorbid condition (Chiang et al 2013;Schaller and Yang 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations